2005
DOI: 10.1371/journal.pgen.0020171.eor
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of Intergenic Transcription: An Evolutionary Comparison

Abstract: Although a large proportion of human transcription occurs outside the boundaries of known genes, the functional significance of this transcription remains unknown. We have compared the expression patterns of known genes as well as intergenic transcripts within the ENCODE regions between humans and chimpanzees in brain, heart, testis, and lymphoblastoid cell lines. We find that intergenic transcripts show patterns of tissue-specific conservation of their expression, which are comparable to exonic transcripts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…These specific expression patterns are reminiscent of genes with regulatory functions and have been considered as one indication of lncRNAs having roles in development and cell identity (Mercer et al , ; Mattick & Dinger, ). However, expression patterns alone are not sufficient to validate function since lncRNAs may theoretically be the result of unspecific transcription from cryptic promoters or intergenic sequences that happen to have high affinity for the transcription machinery (Khaitovich et al , ; Ravasi et al , ; Struhl, ; Ulitsky & Bartel, ). Accordingly, lncRNAs' specific expression patterns would result from cell type, tissue or developmental changes in the chromatin accessibility of the corresponding loci and/or from transcriptional regulatory activity proximal to their loci (Khaitovich et al , ; Ravasi et al , ; Struhl, ).…”
Section: From Genomic Organisation and Expression To Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…These specific expression patterns are reminiscent of genes with regulatory functions and have been considered as one indication of lncRNAs having roles in development and cell identity (Mercer et al , ; Mattick & Dinger, ). However, expression patterns alone are not sufficient to validate function since lncRNAs may theoretically be the result of unspecific transcription from cryptic promoters or intergenic sequences that happen to have high affinity for the transcription machinery (Khaitovich et al , ; Ravasi et al , ; Struhl, ; Ulitsky & Bartel, ). Accordingly, lncRNAs' specific expression patterns would result from cell type, tissue or developmental changes in the chromatin accessibility of the corresponding loci and/or from transcriptional regulatory activity proximal to their loci (Khaitovich et al , ; Ravasi et al , ; Struhl, ).…”
Section: From Genomic Organisation and Expression To Functionmentioning
confidence: 99%
“…Another tissue with widespread expression of lncRNAs with conserved tissue specificity is the testis (Necsulea et al , ; Washietl et al , ). Testis‐specific lncRNAs are enriched in young lncRNAs (Necsulea et al , ) showing greater variability among species than those expressed in other tissues (Khaitovich et al , ). These results are indicative of positive selection (Khaitovich et al , ) and consistent with testis permissive expression leading to new gene origination (Necsulea et al , ).…”
Section: Brain‐specific Lncrnasmentioning
confidence: 99%
See 2 more Smart Citations
“…These intergenic TSSs may either be useless, generating junk RNA transcripts, or useful, that is, as loci‐encoding nonprotein‐coding RNA (ncRNA) transcripts. It has been shown that intergenic‐encoded ncRNAs contribute to functional differences between closely related species, such as humans and chimpanzees (Khaitovich et al, ), pointing to the importance of ncRNA in speciation and in biological processes.…”
Section: Introduction: the Importance Of Nonprotein‐coding Rnasmentioning
confidence: 99%